COba upload - Dewi, Dewi; Bulan, Bulan (Proceedings Series of Educational Studies, 2024)
emocratic parenting is the right parenting to establish independence of student learning. This is done by realizing the existence of deliberations in the family, controlled freedom, exercise responsibility, guidance and direction from parents, parents listen to children's complaints, mutual respect between family members, and two-way communication. In addition, independence of student learning is also influenced by teacher reinforcement, both verbal and nonverbal reinforcement. The purpose of this study is to prove (1) the relationship between parents' democratic parenting and independence of student learning, (2) the relationship between teacher reinforcement and independence of student learning, and (3) the relationship between parents' democratic parenting and teacher reinforcement with independence of student learning. This research was conducted in the School Group 1, Pule District, Trenggalek Regency with the population is 187 people. The approach of this research is quantitative, while the type of this research is the ex post facto correlative research. The research data were obtained using a questionnaire given to the study sample, namely 127 fifth grade students in Cluster 1 Pule District. The statistical analysis used to process data in this study is simple linear regression analysis and multiple linear regression analysis using SPSS 17.0. Based on the results of data analysis, it can be concluded (1) there is a relationship between parents' democratic parenting with independence of student learning with a correlation coefficient 0,474 and a regression equation , (2) there is a relationship between teachers reinforcement with independence of student learning with a correlation coefficient 0,546 and the regression equation , and (3) there is a relationship between parents' democratic parenting and teachers reinforcement with independence of student learning with a correlation coefficient 0,618 and the regression equation . Based on the results of research and conclusions, it is recommended that parents apply democratic parenting so that independence of student learning increases. In addition, the teacher should provide reinforcement to encourage independence of student learning. Schools should create environmental conditions that support increased independence of student learning.